Principles of Pediatric Emergency Care - Meyburg, Jochen (Deutscher Arzte Verlag, 2009)
BACKGROUND: Children account for only a small percentage of pre-hospital emergency patients but are a special challenge for the treating physician. METHODS: The Medline database was selectively searched for articles appearing up to June 2009. The authors added other important literature of which they were aware. RESULTS: The broad spectrum of diseases, the wide age range with the physiological and anatomical changes that occur in it, and the special psychological, emotional, and communicative features of children make pediatric emergencies a special challenge for emergency physicians. CONCLUSIONS: A mastery of basic emergency techniques including clinical evaluation of the child, establishment of venous access, airway management, resuscitation, and drug dosing is essential for the successful emergency treatment of children. We recommend classifying the common non-traumatic pediatric emergencies by four cardinal manifestations: respiratory distress, altered consciousness, seizure, and shock. Classifying these rare emergency situations in this way helps assure that their treatment will be goal-oriented and appropriate to the special needs of sick children.